Formation of the subject domains network on the basis of the ArXiv - Lande, D. V.; Andrushchenko, V. B. (Інститут проблем реєстрації інформації НАН України, 2018)
The new method of information processing, which is based on the Kornuel University Library resource ArXiv is represented. An algorithm of publications search by the given notion taking into conside-ration the research field of the found publication has been developed and actualized. The mail accents were made on the allocation of the publications according to the predefined research fields and appropriate subgroups, established by the resource. Main methods being applied for the realization of the problem are text mining methods and further interpretation of the results, evaluation parameters of the search results.The definition of the subject domains network has been also suggested. For every subject domain predefined by the resource there was formed a vocabulary — a reference tool. The main steps of the subject domains network formation are depicted in the paper.The result of the work is a visual representation of the subjects’ domain network for the concept — «cavitation» and further interpretation of obtained results. For the search results there was calculated the parameter which identify the inherency of the given concept to several subject domain and according to the traditional approaches of the text search evaluation there was calculated the metrics — recall, which characterizes the ability of system to find out the needed documents, but it doesn’t consider the number of non-relevant documents shown to user. The main conclusion of the research is the suggestion of new approaches to form the view on the notion affiliation to several research fields and is based on the open access preprint resource. The developed approach gives an opportunity to analyze, visualize and represent the concept in attribution to research fields; it allows to form the research picture and to widen the ways to form the big projects. Data obtained and represented in the research was processed in February-March, 2018.